Non-significant association between − 330 T/G polymorphism in interleukin-2 gene and chronic periodontitis: findings from a meta-analysis - Felipe Rodolfo Pereira da Silva; Juliana Gomes Galeno; Alessandro Luiz Araújo Bentes Leal; Reyce Santos Koga; Nayana Yared Batista; Silvânia da Conceição Furtado; Daniel Fernando Pereira Vasconcelos; Marcelo Diniz Carvalho; José Fernando Marques Barcellos (BMC, 2020)
Abstract Background Chronic periodontitis (CP) is an immune-inflammatory disease that promotes tissue damage around the teeth. Among the several inflammatory mediators that orchestrate the periodontitis, there is the interleukin (IL)-2. Genetic variations in IL2 gene may be associated with the risk and severity of the disease. Contrary results are available in the literature with inconclusive findings and none meta-analysis to gather these data. Methods A literature search was performed for studies published before June 11, 2019 in diverse scientific and educational databases. The data was extracted by two investigators and the statistical evaluation was performed by Review Manager statistical program with heterogeneity (I2) and Odds Ratio (OR) with 95% of Confidence Intervals (CI) calculations and a sensitive analysis to assess the accuracy of the obtained results. The publication bias was evaluated by Begg' and Egger's test with Comprehensive meta-analysis software. The value of P < 0.05 was considered as significant. Results Five studies were identified in diverse ethnical groups with 1425 participants. The − 330 T/G polymorphism in IL2 gene was not significantly associated with CP in allelic evaluation (P > 0.05) as well as in the genotypic comparisons (P = 0.15). The Begg's test and the linear regression Egger's test did not show any evidence of publication bias risk (P > 0.05) which was corroborated by the absence of obvious asymmetry in Funnel plot graphic. Conclusions This meta-analysis showed a non-significant association between − 330 T/G polymorphism in IL2 gene and CP in any allelic evaluation.